2006
DOI: 10.1111/j.1464-410x.2006.05991.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urinary stone formation in men with spinal cord injury: a 17‐year follow‐up study

Abstract: stone was more common in patients injured when aged ≥ 24 years than in those injured when aged < 24 years (odds ratio 2.5; 95% confidence interval 1.1-5.7; P = 0.03). In another model, patients with complete injury had a greater risk of renal stone formation than those with incomplete injury (4.1, 1.3-12.9; P = 0.016). Renal stone was more common for patients with urethral catheterization than for those voiding spontaneously (5.7, 1.3-24.6, P = 0.021) and for patients with bladder stone than for those without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
(32 reference statements)
0
19
0
2
Order By: Relevance
“…The literature includes inconsistent findings concerning the effect of level and severity of SCI on urinary calculi formation, which complete and high level injuries have been found associated with urinary calculi in some studies. [10][11][12] In the present study, urinary calculi were more frequent in patients with tetraplegia than those with paraplegia. But, these associations remained non-significant in the logistic regression analysis.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The literature includes inconsistent findings concerning the effect of level and severity of SCI on urinary calculi formation, which complete and high level injuries have been found associated with urinary calculi in some studies. [10][11][12] In the present study, urinary calculi were more frequent in patients with tetraplegia than those with paraplegia. But, these associations remained non-significant in the logistic regression analysis.…”
Section: Discussionmentioning
confidence: 60%
“…8,15 Bartel et al 5 noted bladder calculi by IUC in 6.6% and by CIC in 2%. Chen et al 14 found that IUC was associated with a substantially greater risk of bladder calculi; however, Ku et al 12 did not show this relationship with bladder calculi. In the present study, bladder calculi was observed 3.8% in spontaneous/other, 6.1% in CIC and 9.3% in IUC, although renal calculi had similar incidence rates among bladder management methods.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations